Society shapes industrial policy, industrial policy shapes society - Aiginger, Karl (Archives of Business Research, 2022)
Industrial Policy has been defined and performed in very different ways over time and across countries and continents, along with its aims and scope. Instead of repeating these controversies, the article starts with the emerging consensus that systemic industrial policy should support societal priorities and that instruments should be used which maximize synergies with other policy strands. A future-oriented industrial policy should also no longer maximize national priorities, but goals should at least be shared with neighboring countries. Realistically, we have to acknowledge that it will remain a weapon in the competition between superpowers and those who want to defend or gain this status. Industrial Policy will also be different in emerging countries with low income and education, a high agricultural share, and persistent gender differences, compared to that in highly industrialized countries. Industrial policy leads to and requires structural change, with causality running in both directions. Its shape will influence the "future of capitalism", and the socio-ecological system will define the content of a systemic and integrated industrial policy.